Diagnosis, Diagnostic Tools, and Risk Stratification for Contemporary Treatment of Pulmonary Embolism - Remillard, Taylor C.; Kodra, Arber; Kim, Michael (International Journal of Angiology, 2022)
Pulmonary embolism (PE) is quite common and is associated with significant morbidity and mortality. It is estimated that it is the cause of approximately 100,000 annual deaths in the United States. With great variability in presenting symptoms of PE, poor recognition of PE can be fatal. As such, many risk scores have been created to identify the sickest patients. Choosing the appropriate imaging modality is also critical. Invasive pulmonary angiography was once the gold standard to establish the diagnosis. With the advent of nuclear imaging, V/Q scans, invasive angiography has been phased out for diagnosing acute PE. At present, the standard for diagnosis of acute PE is computed tomography pulmonary angiography. In select patient cohorts, nuclear studies remain the modality of choice. Once the diagnosis of acute PE is established, there is a broad spectrum of severity in outcome which has led to substantial focus and development of risk stratification prediction models. We will discuss making the proper diagnosis with contemporary diagnostic tools and risk stratifying patients with PE to receive the correct treatment.
Keywords: pulmonary embolism; risk stratification; right ventricular strain; V/Q scan; computed tomography pulmonary angiography; echocardiography